TECHNICAL GUIDANCE ON BIOPORE HOLES SOIL CONSERVATION AS ONE OF THE FLOOD PREVENTION EFFORTS FOR THE COMMUNITY OF PIRAK TIMU DISTRICT, NORTH ACEH REGENCY: PENDAMPINGAN TEKNIK KONSERVASI TANAH LOBANG BIOPORI SEBAGAI SALAH SATU UPAYA PENCEGAHAN BANJIR KEPADA MASYARAKAT KECAMATAN PIRAK TIMU KABUPATEN ACEH UTARA - Halim Akbar; Sakral Hasby Puarada; Muhammad Authar ND; Riris Nadia Syafrilia Gurning (PT. ROCE WISDOM ACEH, 2024)
Flood control is mainly related to the behavior of residents in a watershed, namely,how each resident in a watershed wants to build an inundation system and/orabsorption system (through soil conservation technology) on their respective plotsof land. There are at least two approaches to understanding this aspect of behavior,namely the normative approach and the rational choice approach. In thesocialization, they conveyed the importance of understanding land conservation inorder to save the environment and the flood mitigation process. The team alsoprovided an introduction to a soil drilling tool which is useful for making bioporeholes, providing felt (dry leaves) in holes that have been planted with perforatedpipes with the aim of reducing surface flow, creating water absorption which willlater be used to reserve water in the soil and reduce surface flow with the aim ofstimulating microorganisms such as worms so as to eliminate flooding. Next, theteam evaluated when it rained. This test is carried out to see the progress ofwhether there are any changes in the land that has been given such treatment. Thecommunity is very enthusiastic because this is a big motivation for the communityto grow crop